Knowledge, Attitude and Practice of Female Nurses on Complementary Feeding in a Tertiary level Hospital of Bangladesh (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: Inadequate knowledge on nutritious foods and feeding practices are determinant of malnutrition rather than lack of food. Health professionals particularly nurses pass long contact time with the mothers, so positive attitude among them can be used in motivating mothers for infant and young child feeding. There is little data available in this regard, therefore evaluation of nurses’ knowledge, attitude and practice on complementary feeding is very important. This study was conducted among the female nurses in a tertiary level hospital of Bangladesh to find out the knowledge, attitude and practice of complementary feeding to their own under-2 children. Methods: The descriptive study was carried out at Dhaka Medical College Hospital between September 2014 and August 2015. Total 95 nurses having children from 6 months up to 2 years of age were enrolled as sample.Results: It showed that 63.1% of the nurses had good understanding on complementary feeding. But 46.3% of them did not know the duration correctly and 27.4% considered infant formula as the complementary food. Almost all had the positive attitude but 28.4% stated that distraction during feeding is needed. Among the respondents, 97% strongly agreed about the importance of complementary feeding but 67.4% of the nurses introduced complementary food before 6 months of age. Only 58.9% of them continued breast feeding up to 2 years.Conclusion: The study reflects that although most of the nurses have adequate knowledge and positive attitude towards complementary feeding but deviation was noted in timely Introduction of complementary food and use of feeding bottle. This indicates clear disparity between knowledge and practice of the female nurses.J Bangladesh Coll Phys Surg 2022; 40: 87-92